Lightning Injury in Indoor Setting - A Case Report - Biswas, Sarmistha; Karim, Md Enamul; Chowdhury, Joybaer Anam; Sarkar, Prodip Kumar; Begum, Mahmuda; Sarkar, Md Mahfuze; Bardhan, Supta; Dey, Uttam Kumar; Bala, Chandra Shekhor (Journal of Dhaka Medical College, 2016)
Lightning strike is a common disaster in Bangladesh. The number of deaths and injuries due to lightning in Bangladesh is over 150 per annum as reported in the newspapers. However, this number may be several times higher as information network in the country is mediocre. The mortality following lightning strike is 10% to 30%. Most of the casualties occur in an outdoor setting; indoor accidents are much less. A survival case of thunderbolt injury in an indoor setting admitted in Dhaka Medical College, Dhaka, has been reported here J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 79-81